2017
DOI: 10.1002/adma.201704362
|View full text |Cite|
|
Sign up to set email alerts
|

Giant Magnetic Heat Induction of Magnesium‐Doped γ‐Fe2O3 Superparamagnetic Nanoparticles for Completely Killing Tumors

Abstract: Magnetic fluid hyperthermia has been recently considered as a Renaissance of cancer treatment modality due to its remarkably low side effects and high treatment efficacy compared to conventional chemotheraphy or radiotheraphy. However, insufficient AC induction heating power at a biological safe range of AC magnetic field (H ·f < 3.0-5.0 × 10 A m s ), and highly required biocompatibility of superparamagnetic nanoparticle (SPNP) hyperthermia agents are still remained as critical challenges for successful clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 36 publications
3
68
1
1
Order By: Relevance
“…The XPS spectra (Figure S2b ) confirmed the presence of Fe(III) in the film with peaks at 710 and 724 eV (Fe 2p 1/2 and 2p 3/2 ), and the disappearance of peaks around 91 eV (for gold) indicated that the SM( 5 )-[ 5 ] 5 film was stable against X-ray irradiation, and the film thickness was greater than the sampling depth of XPS (8~10 nm) 29 . In addition, the stoichiometry of Fe(III) and TA in the films was calculated to be about 4:1 based on narrow-scan XPS spectra, which was similar to the Fe(III)-TA-MOC films formed by multi-step LbL deposition 14 and biphasic interfacial assembly 23 .…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The XPS spectra (Figure S2b ) confirmed the presence of Fe(III) in the film with peaks at 710 and 724 eV (Fe 2p 1/2 and 2p 3/2 ), and the disappearance of peaks around 91 eV (for gold) indicated that the SM( 5 )-[ 5 ] 5 film was stable against X-ray irradiation, and the film thickness was greater than the sampling depth of XPS (8~10 nm) 29 . In addition, the stoichiometry of Fe(III) and TA in the films was calculated to be about 4:1 based on narrow-scan XPS spectra, which was similar to the Fe(III)-TA-MOC films formed by multi-step LbL deposition 14 and biphasic interfacial assembly 23 .…”
Section: Introductionsupporting
confidence: 54%
“…The material-independent, universal Fe(III)-TA nanocoating has been demonstrated with a multitude of substrates, including planar and particulate ones 13 16 , viruses 18 and living cells 19 21 , and dentinal tubules 22 . The Fe(III)-TA-MOC also has recently been utilized for biphasic interfacial film formation, such as hollow microcapsules in the water-oil biphasic system 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, special attention has been paid to the development of high‐performance thermal agents. However, it seems such research was only restricted to the MNPs . Though termed as “magnetic‐mediated hyperthermia,” it should be clarified that “magnetic” does not necessarily limit the choice of the thermal agents only within magnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…One of the aims in developing magnetothermal therapies is to enhance the heating efficiency of MIONs in order to reach desirable temperature with minimum dosage and power density. Recent progress in optimizing MIONs, such as synthesizing anisotropic MIONs, 31 nanoassembly, 70 core‐shell nanostructures, 71 and ion‐doped MIONs, 72 has achieved unprecedented magnetic heating efficiency (>1 kW/g). However, the dynamical magnetic response of MIONs is confined by the complex biological environments.…”
Section: Mions For Cancer Diagnosis and Therapymentioning
confidence: 99%